Crossroads of Ecology and Medicine: Evaluating Pollutant-Induced Risks to Biodiversity and Human Health - Satish Kumar Sarankar; Sushma Somkuwar (International Journal of Environmental Noise and Pollution Control, 2025)
Environmental pollution has emerged as a central challenge at the crossroads of ecology and human medicine. The rapid pace of industrialization, urbanization, and agricultural intensification has led to an unprecedented release of pollutants into the air, water, and soil—triggering cascading effects on ecosystems and human health. Pollutants such as particulate matter, heavy metals, pesticides, microplastics, endocrine-disrupting chemicals, and persistent organic pollutants not only degrade biodiversity but also exert multifaceted health risks across populations. This review provides an interdisciplinary evaluation of the pathways through which environmental contaminants influence both ecological balance and human physiology. Pollution-induced oxidative stress, endocrine disruption, neurotoxicity, genotoxicity, and immune suppression form the core biological mechanisms behind rising incidences of chronic diseases, including asthma, cardiovascular illness, reproductive dysfunctions, neurological impairments, and cancers. Simultaneously, biodiversity decline resulting from pollutant exposure—undermines ecosystem services such as pollination, disease regulation, and food security, indirectly threatening public health. Notably, microbial diversity losses impact gut and soil health, disrupting human immunity and agricultural productivity. Vulnerable groups, including children, the elderly, low-income populations, and occupationally exposed workers, face disproportionate burdens. Real-world examples, such as the health crises in Flint, Michigan and Bhopal, India, highlight the lasting consequences of unchecked pollutant exposure. Additionally, climate change exacerbates these effects by altering pollutant dynamics and increasing exposure unpredictability. Clinical and public health responses have made strides, exemplified by global policy initiatives like the Clean Air Act and Minamata Convention. However, the integration of environmental risk assessments into routine healthcare remains limited. This article emphasizes the urgent need for systemic interventions—including environmental surveillance, green urban planning, sustainable technologies, and pollution-conscious clinical care. Furthermore, the integration of ecological and health sciences in research, education, and policy-making is critical for fostering long-term resilience. Pollutants represent a shared threat to ecosystems and human populations, necessitating cross-sectoral collaboration, enhanced regulatory frameworks, and equitable public health strategies. Only through a unified, globally informed response can we mitigate pollutant-induced risks and promote a future that protects both biodiversity and human well-being.
Keywords: Biodiversity loss; Environmental pollution; climate change and public health; ecotoxicology; human health; pollution policy